IMPLEMENTASI SUPERVISI PENGAWAS MADRASAH DALAM PENINGKATAN KINERJA KEPALA MADRASAH - Nugraha, Doni; Ayu Lestari (Program Studi Manajemen Pendidikan Islam, 2025)
In the era of globalization, the demand for quality education is increasing, making the role of madrasah principals as the spearhead of educational management very strategic in efforts to enhance the quality of education in madrasahs. The effective performance of madrasah principals is closely linked to the supervision conducted by madrasah supervisors, who are responsible for mentoring, monitoring, and evaluating the tasks of madrasah principals. This study aims to (1) describe the implementation of madrasah supervisor supervision in improving the performance of madrasah principals at MTs. Jidris Assalam, Purbaratu District, Tasikmalaya City, (2) describe the evaluation of madrasah supervisor supervision in enhancing the performance of madrasah principals at MTs. Jidris Assalam, Purbaratu District, Tasikmalaya City, and (3) describe the impact of madrasah supervisor supervision on the performance of madrasah principals at MTs. Jidris Assalam, Purbaratu District, Tasikmalaya City. The research method used is a case study with a descriptive qualitative approach. Data were collected through direct observation, in-depth interviews with madrasah supervisors, madrasah principals, and relevant staff, as well as relevant documentation. Data analysis was conducted descriptively by examining the information obtained to provide a comprehensive picture of the implementation, evaluation, and impact of supervision on the performance of madrasah principals. The results of the study indicate that the supervision of madrasah supervisors is carried out periodically and effectively, providing guidance and oversight that contribute to the improvement of professionalism and performance of madrasah principals. The evaluation of supervision shows an increase in the performance of madrasah principals, reflected in the very good performance assessment scores. The impact of this supervision is evident in the enhancement of the leadership of madrasah principals, which supports the achievement of educational goals in madrasahs. Thus, the supervision of madrasah supervisors becomes a key factor in improving the quality of the performance of madrasah principals and the quality of education in madrasahs.